2021
DOI: 10.1590/0047-2085000000306
|View full text |Cite
|
Sign up to set email alerts
|

Percepção do medo de ser contaminado pelo novo coronavírus

Abstract: RESUMO Objetivo: Avaliar a prevalência e os fatores associados à percepção do medo de ser contaminado pelo novo coronavírus. Métodos: Estudo transversal realizado em Passo Fundo, Rio Grande do Sul, com indivíduos de ambos os sexos e 18 ou mais anos de idade. Coleta on-line de dados sociodemográficos, de saúde, de comportamento e de conhecimento acerca do vírus. Análise estatística descritiva e cálculo de prevalência e de razões de prevalência (RP) brutas e ajustadas. Resultados: Amostrados 920 participantes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
2
0
3
Order By: Relevance
“…This study has identi ed that 64% of the total sample reported feeling very afraid of being contaminated. In addition to the selfperception of the risk of being infected, other elements were associated with the perception of fear, such as the perception of health and the adoption of preventive measures against Covid-19 [32]. In our results, more than half of the participants indicated fear of being infected, although the objective assessment of fear is di cult to perform because the feeling of fear is a subjective and adaptive characteristic [33].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This study has identi ed that 64% of the total sample reported feeling very afraid of being contaminated. In addition to the selfperception of the risk of being infected, other elements were associated with the perception of fear, such as the perception of health and the adoption of preventive measures against Covid-19 [32]. In our results, more than half of the participants indicated fear of being infected, although the objective assessment of fear is di cult to perform because the feeling of fear is a subjective and adaptive characteristic [33].…”
Section: Discussionmentioning
confidence: 61%
“…A recent cross-sectional study carried out with 756 participants has shown the prevalence and associated factors with the fear perception of being infected by the new coronavirus [32]. This study has identi ed that 64% of the total sample reported feeling very afraid of being contaminated.…”
Section: Discussionmentioning
confidence: 96%
“…The high number of cases and deaths, all the information disseminated by the media and propagated through social networks, the lack of a specific antiviral treatment for the disease and false information regarding effectiveness of the vaccines contributed to generalizing fear regarding COVID-19 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Toda atividade humana é um ato produtivo realizado em conjunto, sua organização possibilita compreendermos a sociedade em que vivemos, pois afeta nossa forma de agir e pensar. As formas de organização social e do trabalho se alteram mediante mudanças ocorridas na sociedade no decorrer do tempo, o trabalho é produtor de valores de uso e de troca, adaptando-se às novas necessidades 23 .…”
Section: O Trabalho Vivo Em Atounclassified